Comparison of nonsurgical periodontal therapy with hand scaler, conventional ultrasonic scaler, and vector™ ultrasonic system in patients with generalized chronic periodontitis - Ashutosh Nirola; Priyanka Batra; Sharanbir Kaur (Wolters Kluwer Medknow Publications, 2016)
Background: The purpose of the study was to compare clinical efficacy of nonsurgical periodontal therapy with hand scaler, conventional ultrasonic scaler, and Vector™ ultrasonic system in patients with generalized chronic periodontitis. Materials and Methods: Sixty patients with generalized chronic periodontitis fitting the inclusion and exclusion criteria were assigned to one of the three treatment groups (n = 20 in each group). Group I - hand scalers, Group II - conventional ultrasonic scalers, and Group III - Vector™ ultrasonic system. Before oral prophylaxis, clinical parameters (gingival index [GI], plaque index [PI], calculus index [CI], periodontal probing depth [PPD], clinical attachment loss [CAL], and hypersensitivity) were recorded. GI, PI, CI, and hypersensitivity were reevaluated at 1, 3, 6 and 12 weeks. PPD and CAL were reevaluated at 6 and 12 weeks. Results and Conclusion: The results showed that nonsurgical therapy with Vector™ ultrasonic system is clinically comparable in all the parameters, to hand and conventional ultrasonic scalers, suggesting that it can be used as a gentle root debridement device for supportive periodontal therapy, as an alternative to other ultrasonic or sonic scalers.